RAMIPRIL IN THERAPY OF PATIENTS AFTER MYOCARDIAL INFARCTION - I. V. Szirov; E. V. Malichenko (Столичная издательская компания, 2015)
Angiotensin converting enzyme inhibitors are the first line medicine for the treatment of the most of cardiovascular diseases. There is no class-effect for these drugs in myocardial infarction therapy. Moreover in myocardial infarction angiotensin converting enzyme inhibitors have significant intra-group differences. Ramipril is the one of the most studied drug of this group recommended for patients after acute myocardial infarction.